(untitled) (Journal of Atomic and Molecular Sciences, 2021)
4-hydroxy-l-proline is formed by hydroxylation of proline, an amino acid found in protein, whose inhibition results in hair problems in human, causing scurvy disease. We report a theoretical study on cis and trans conformers of 4-hydroxy-l-proline using first principle density functional approach at B3LYP/6-31+G(d,p) level. The equilibrium structures of both conformers are obtained to analyze their vibrational properties. The calculated vibrational modes are assigned and interpreted on the basis of potential energy distribution analysis. A good correlation has been obtained between calculated frequencies and corresponding experimental values from FTIR spectra. The electronic properties of both conformers are also calculated and discussed.